(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
This study starts with an examination of worldwide issues affecting teaching, especially as they relate to knowledge and career opportunities. A variety of philosophical viewpoints and debates are examined in order to address these issues, including classic romantic and institutional conceptions of education, as well as more contemporary realist, neoliberalism, laboratory, and post modern viewpoints on continuous learning. We argue In this paper, we argue that it’s not the "last word" on maintaining and growing equality of opportunity, and instead offer an alternative perspective based on the concept of using an inclusive real concern framework, which we suspect is better equipped to having provided solutions for a wide range of global problems that have been identified or that are still being identified. We believe that such a system addresses and expands the individual, social, socioeconomic, and political dimensions of education, leading to better learning and life outcomes opportunities.